A Gamified Approach to Engage Sustainable User Behavior in Product Service System Solutions - Villamil, Carolina (European Journal of Sustainable Development, 2023)
Product service system solutions encourage to share products, reducing manufacturing processes and increasing the product life. Therefore, this might contribute to offer more sustainable solutions to users, by considering the complete socio-ecological system, the context, the stakeholder relationship, among other aspects. Where the sustainability behavior of consumers and the data provided for new information and technology (ICT) devices are key factors in the development of solutions with a higher sustainability performance. Moreover, game elements and ICT have been used in different fields to engage users. The aim of this research is to investigate if a gamified approach motivates a substantiable behavior change in users of product service system solutions. Based on a literature review, a model is proposed and applied to a product service system case of a shared laundry facility in Sweden. The model was evaluated with experts semi-structured interviews and a survey with users of the shared laundry facility. Concluding that a gamified approach has a potential to motivate behavior change towards sustainability in product service system. In future research, the proposed model will be adapted to be tested in other product service system cases, with the purpose to improve it for its application in industry and education. Keywords: strategic sustainable development, game elements, product development, smart PSS, behavior change.